Managing electronic serials : - Bluh, Pamela (American Library Association, 2001)
Contain includes: staffing appropriately for fast-changing technology; scrutinizing content of potential acquisitions; negotiating licensing arrangements; avoiding copyright pitfalls; enhancing value with hypertext links.